A TOPCon cell front anti-reflection film structure and preparation method thereof

By improving the stacked structure of the front anti-reflection film structure of the TOPCon battery, the refractive index and thickness of the front silicon nitride layer are reduced, and the problem of high refractive index and reflectivity in the prior art affecting the efficiency of the battery is solved, thereby achieving higher light absorption and conversion efficiency.

CN119767874APending Publication Date: 2025-04-04宜宾英发德耀科技有限公司
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411862517.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The high refractive index and reflectivity of the front anti-reflection film structure of the existing TOPCon battery affect the absorption of front light and reduce the conversion efficiency of the battery.

Method used

By changing the structure of the front anti-reflection film, the refractive index and thickness of the front silicon nitride layer are improved from a conventional stacked structure of three layers of silicon nitride + two layers of silicon nitride oxide + one layer of silicon oxide to a stacked structure of two layers of silicon nitride + one layer of silicon nitride oxide + one layer of silicon oxide.

Benefits of technology

It achieves a lower front refractive index and reflectivity, enhances the absorption of front light, significantly improves the conversion efficiency of the battery, and retains a good passivation effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119767874A_ABST
    Figure CN119767874A_ABST
Patent Text Reader

Abstract

The present application proposes a TOPCon cell front anti-reflection film structure and a preparation method thereof, and relates to the technical field of TOPCon cell preparation. A TOPCon cell front anti-reflection film structure comprises a silicon substrate and an aluminum oxide layer arranged on the silicon substrate, and the aluminum oxide layer is also sequentially arranged with a first silicon nitride layer, a second silicon nitride layer, a silicon oxynitride layer and a silicon oxide layer. The present application changes the structure of the front anti-reflection film (from the conventional three-layer silicon nitride + two-layer silicon oxynitride + one-layer silicon oxide laminated structure to a two-layer silicon nitride + one-layer silicon oxynitride + one-layer silicon oxide laminated structure), the total thickness of the structure remains unchanged, but the refractive index and thickness of the front silicon nitride layer are reduced, and the refractive index of the total front structure is reduced from the original 2.08 to 2.0; the absorption of the front light is enhanced, the optical effect is significantly improved, and at the same time, a good passivation effect is retained, so that the short-circuit current gain is obvious, and the conversion efficiency is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of TOPCon cell preparation, and in particular to a TOPCon cell front anti-reflection film structure and a preparation method thereof. Background Art

[0002] Tunnel Oxide Passivated Contact solar cell (TOPcon) is a new type of passivated contact solar cell first proposed by the Fraunhofer Institute for Solar Energy in Germany at the 28th European PVSEC Photovoltaic Conference in 2013. As a high-efficiency solar cell technology, photovoltaic TOPCon solar cells have higher conversion efficiency and lower energy costs and have received widespread attention.

[0003] The structure of a TOPcon cell usually includes a silicon wafer, the front side of which is stacked with a boron diffusion layer, a passivation layer, a front anti-reflection layer, and a front electrode, and the back side of which is stacked with a tunneling oxide layer, a (doped) polysilicon layer, a back anti-reflection layer, and a back electrode. The tunneling oxide layer and the (doped) polysilicon layer on the back side of the cell together form a passivation contact structure, providing good interface passivation for the back side of the silicon wafer. In particular, the N-type TOPCon cell has a lower boron content in phosphorus-doped N-type crystalline silicon than the P-type PERC cell (Passivated Emitter Rear Cell, passivated reflector and back cell structure), and has a better passivation effect.

[0004] TOPCON battery technology is the mainstream mass-produced technology in the industry, and the improvement of its conversion efficiency is the focus of attention of all parties in the industry. The main direction of efficiency improvement is to reduce optical loss and electrical loss, thereby increasing the open circuit voltage and short circuit current of the battery cell. At present, the front anti-reflection film in the industry mostly adopts a stacked structure of silicon nitride / silicon oxynitride / silicon oxide. The main function of the front anti-reflection film is passivation and anti-reflection, that is, to increase the open circuit voltage and short circuit current. Traditional PREC cells are P-type substrates with serious boron-oxygen recombination, so the PID effect is poor, and the refractive index of the front anti-reflection film needs to be increased to improve PID. At present, most conventional anti-reflection films in the industry have high refractive indices. High refractive index means high reflectivity, which will affect the absorption of front light, reduce the short-circuit current of the battery, and affect battery efficiency. Summary of the invention

[0005] The purpose of the present application is to provide a TOPCon cell front anti-reflection film structure, which has a lower front refractive index and reflectivity, enhances the absorption of front light, and improves conversion efficiency.

[0006] Another object of the present application is to provide a method for preparing a front anti-reflection film structure of a TOPCon cell, which is simple and convenient.

[0007] In order to solve the above technical problems, the technical solution adopted in this application is:

[0008] On the one hand, the present application provides a TOPCon cell front anti-reflection film structure, comprising a silicon substrate 1 and an aluminum oxide layer 2 arranged on the silicon substrate 1, wherein a first silicon nitride layer 3, a second silicon nitride layer 4, a silicon oxynitride layer 5 and a silicon oxide layer 6 are sequentially arranged on the aluminum oxide layer 2.

[0009] On the other hand, the present application provides a method for preparing a front anti-reflection film structure of a TOPCon cell, comprising the following steps:

[0010] S1, first depositing an aluminum oxide layer 2 on the front surface of a silicon substrate 1;

[0011] S2, depositing a first silicon nitride layer 3 on the aluminum oxide layer 2, wherein the silicon-nitrogen ratio is 15%-17%;

[0012] S3, depositing a second silicon nitride layer 4 on the first silicon nitride layer 3, wherein the silicon-nitrogen ratio is 10%-12%;

[0013] S4, depositing a silicon oxynitride layer 5 on the second silicon nitride layer 4, wherein the silicon-nitrogen ratio is 17%-19%, and the optimal value is 18%;

[0014] S5, depositing a silicon oxide layer 6 on the silicon oxynitride layer 5, wherein the silicon-nitrogen ratio is 8%-10%, and the optimal value is 9%;

[0015] Compared with the prior art, the embodiments of the present application have at least the following advantages or beneficial effects:

[0016] The present application changes the structure of the front anti-reflection film (from the conventional stacked structure of three layers of silicon nitride + two layers of silicon oxynitride + one layer of silicon oxide to a stacked structure of two layers of silicon nitride + one layer of silicon oxynitride + one layer of silicon oxide), and the total thickness of the structure remains unchanged, but the refractive index and thickness of the front silicon nitride layer are reduced (from the traditional 52nm to 34nm in the present application), and the refractive index of the total front structure is reduced from the original 2.08 to 2.0; because the TOPCON battery has an N-type substrate and does not have boron-oxygen composites, it has a better anti-PID effect, so this improvement will not have side effects on the battery cell, but enhances the absorption of front light, significantly improves the optical effect, and retains a good passivation effect, so that its short-circuit current gain is obvious, and the conversion efficiency is greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 This is a schematic cross-sectional diagram of the front anti-reflection film structure of the experimental group in the experimental example of this application;

[0019] Figure 2 This is a schematic cross-sectional diagram of the front anti-reflection film structure of the control group in the experimental example of this application.

[0020] Symbols in the figure: 1-silicon substrate; 2-aluminum oxide layer; 3-first silicon nitride layer; 4-second silicon nitride layer; 5-silicon oxynitride layer; 6-silicon oxide layer; 7-third silicon nitride layer; 8-second silicon oxynitride layer. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0022] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to specific embodiments.

[0023] A TOPCon cell front anti-reflection film structure comprises a silicon substrate 1 and an aluminum oxide layer 2 arranged on the silicon substrate 1, wherein a first silicon nitride layer 3, a second silicon nitride layer 4, a silicon oxynitride layer 5 and a silicon oxide layer 6 are sequentially arranged on the aluminum oxide layer 2.

[0024] In some embodiments of the present application, the thickness of the first silicon nitride layer 3 is 10-14nm, preferably 12nm; the thickness of the second silicon nitride layer 4 is 20-24nm, preferably 22nm; the thickness of the silicon oxynitride layer 5 is 24-28nm, preferably 26nm; the thickness of the silicon oxide layer 6 is 12-16nm, preferably 14nm.

[0025] A method for preparing a front anti-reflection film structure of a TOPCon cell comprises the following steps:

[0026] S1, first depositing an aluminum oxide layer 2 on the front surface of a silicon substrate 1;

[0027] S2, depositing a first silicon nitride layer 3 on the aluminum oxide layer 2, wherein the silicon-nitrogen ratio is 15%-17%, preferably 16%;

[0028] S3, depositing a second silicon nitride layer 4 on the first silicon nitride layer 3, wherein the silicon-nitrogen ratio is 10%-12%, preferably 11%;

[0029] S4, depositing a silicon oxynitride layer 5 on the second silicon nitride layer 4, wherein the silicon-nitrogen ratio is 17%-19%, and the optimal value is 18%;

[0030] S5. Depositing a silicon oxide layer 6 on the silicon oxynitride layer 5, wherein the silicon-nitrogen ratio is 8%-10%, and the optimal value is 9%.

[0031] In some embodiments of the present application, the deposition parameters of the above-mentioned S2 step are: silane flow rate 1600-1800sccm, ammonia flow rate 10000-11250sccm, optimal value 10465sccm, deposition time 150-170s, optimal value 160s.

[0032] In some embodiments of the present application, the deposition parameters of the above-mentioned step S3 are: silane flow rate 1000-1300sccm, the optimal value is 1150sccm; ammonia flow rate 10000-13000sccm, the optimal value is 10915sccm; deposition time 280-320s, the optimal value is 300s.

[0033] In some embodiments of the present application, the deposition parameters of the above-mentioned S4 step are: silane flow rate 1000-1200sccm, the optimal value is 1100sccm; ammonia flow rate 4900-5500sccm, the optimal value is 5200sccm; nitrous oxide flow rate 7000-7800sccm, the optimal value is 7400sccm; deposition time 200-240s, the optimal value is 220s.

[0034] In some embodiments of the present application, the deposition parameters of the above-mentioned step S5 are: silane flow rate 800-100 sccm, the optimal value is 900 sccm; nitrous oxide flow rate 11200-12200 sccm, the optimal value is 11700 sccm; deposition time is 160-200 s, the optimal value is 180 s.

[0035] The features and performance of the present application are further described in detail below in conjunction with the embodiments.

[0036] Example 1

[0037] This embodiment provides a TOPCon cell front anti-reflection film structure, comprising a silicon substrate 1 and an aluminum oxide layer 2, a first silicon nitride layer 3, a second silicon nitride layer 4, a silicon oxynitride layer 5 and a silicon oxide layer 6 sequentially deposited on the silicon substrate 1. The specific preparation process is as follows:

[0038] S1, first depositing an aluminum oxide layer 2 on the front surface of a silicon substrate 1;

[0039] S2, depositing a first silicon nitride layer 3 on the aluminum oxide layer 2: silane flow rate is 1700 sccm, ammonia flow rate is 10465 sccm, deposition time is 160 s, silicon-nitrogen ratio is 16%, and the thickness of the first silicon nitride layer 3 is 12 nm;

[0040] S3, depositing a second silicon nitride layer 4 on the first silicon nitride layer 3: silane flow rate 1150 sccm, ammonia flow rate 10915 sccm, deposition time 300 s, silicon-nitrogen ratio 11%; the thickness of the second silicon nitride layer 4 is 22 nm;

[0041] S4, depositing a silicon oxynitride layer 5 on the second silicon nitride layer 4: silane flow rate 1200 sccm, ammonia flow rate 5200 sccm, nitrous oxide flow rate 7400 sccm, deposition time 215 s; the thickness of the silicon oxynitride layer 5 is 26 nm;

[0042] S5. Depositing a silicon oxide layer 6 on the silicon oxynitride layer 5: silane flow rate is 900 sccm, nitrous oxide flow rate is 11700 sccm, and deposition time is 175 s; the thickness of the silicon oxide layer 6 is 14 nm.

[0043] Example 2

[0044] This embodiment provides a TOPCon cell front anti-reflection film structure, comprising a silicon substrate 1 and an aluminum oxide layer 2, a first silicon nitride layer 3, a second silicon nitride layer 4, a silicon oxynitride layer 5 and a silicon oxide layer 6 sequentially deposited on the silicon substrate 1. The specific preparation process is as follows:

[0045] S1, first depositing an aluminum oxide layer 2 on the front surface of a silicon substrate 1;

[0046] S2, depositing a first silicon nitride layer 3 on the aluminum oxide layer 2: silane flow rate is 1800 sccm, ammonia flow rate is 11065 sccm, deposition time is 165 s, silicon-nitrogen ratio is 16%, and the thickness of the first silicon nitride layer 3 is 13 nm;

[0047] S3, depositing a second silicon nitride layer 4 on the first silicon nitride layer 3: silane flow rate 1200 sccm, ammonia flow rate 11515 sccm, deposition time 320 s, silicon-nitrogen ratio 10%; the thickness of the second silicon nitride layer 4 is 24 nm;

[0048] S4, depositing a silicon oxynitride layer 5 on the second silicon nitride layer 4: silane flow rate 1100 sccm, ammonia flow rate 5300 sccm, nitrous oxide flow rate 7300 sccm, deposition time 220 s; the thickness of the silicon oxynitride layer 5 is 26 nm;

[0049] S5. Depositing a silicon oxide layer 6 on the silicon oxynitride layer 5: silane flow rate is 950 sccm, nitrous oxide flow rate is 12000 sccm, and deposition time is 180 s; the thickness of the silicon oxide layer 6 is 15 nm.

[0050] Example 3

[0051] This embodiment provides a TOPCon cell front anti-reflection film structure, comprising a silicon substrate 1 and an aluminum oxide layer 2, a first silicon nitride layer 3, a second silicon nitride layer 4, a silicon oxynitride layer 5 and a silicon oxide layer 6 sequentially deposited on the silicon substrate 1. The specific preparation process is as follows:

[0052] S1, first depositing an aluminum oxide layer 2 on the front surface of a silicon substrate 1;

[0053] S2, depositing a first silicon nitride layer 3 on the aluminum oxide layer 2: silane flow rate is 1750 sccm, ammonia flow rate is 12000 sccm, deposition time is 170 s, silicon-nitrogen ratio is 15%, and the thickness of the first silicon nitride layer 3 is 14 nm;

[0054] S3, depositing a second silicon nitride layer 4 on the first silicon nitride layer 3: silane flow rate 1250 sccm, ammonia flow rate 10925 sccm, deposition time 310 s, silicon-nitrogen ratio 11%; the thickness of the second silicon nitride layer 4 is 21 nm;

[0055] S4, depositing a silicon oxynitride layer 5 on the second silicon nitride layer 4: silane flow rate 1150 sccm, ammonia flow rate 5500 sccm, nitrous oxide flow rate 7600 sccm, deposition time 210 s; the thickness of the silicon oxynitride layer 5 is 26 nm;

[0056] S5. Depositing a silicon oxide layer 6 on the silicon oxynitride layer 5: silane flow rate is 950 sccm, nitrous oxide flow rate is 12000 sccm, and deposition time is 200 s; the thickness of the silicon oxide layer 6 is 16 nm.

[0057] Experimental example

[0058] This experimental example compares the conventional TOPCon cell front anti-reflection film structure (control group) with the improved anti-reflection film structure of the present application (experimental group).

[0059] The conventional TOPCon cell front anti-reflection film structure is as follows: Figure 2 As shown, an aluminum oxide layer 2, a first silicon nitride layer 3 (9 nm thick), a second silicon nitride layer 4 (15 nm thick), a third silicon nitride layer 7 (28 nm thick), a silicon oxynitride layer 5 (8 nm thick), a second silicon oxynitride layer 8 (11 nm thick) and a silicon oxide layer 6 (3 nm thick) are sequentially arranged on a silicon substrate 1, with a total film thickness of 74 nm and a refractive index of 2.08. The specific preparation process is:

[0060] The deposition time of the first silicon nitride layer 3 is 110s, the silane flow rate is 2800sccm, the ammonia flow rate is 10000sccm, and the silicon-nitrogen ratio is 28%; the deposition time of the second silicon nitride layer 3 is 320s, the silane flow rate is 2000sccm, the ammonia flow rate is 11800sccm, and the silicon-nitrogen ratio is 17%; the deposition time of the third silicon nitride 7 is 200s, the silane flow rate is 1400sccm, the ammonia flow rate is 13580sccm, and the silicon-nitrogen ratio is 10%; The deposition time of the silicon oxynitride layer 5 is 110s, the silane flow rate is 1200sccm, the ammonia flow rate is 5200sccm, and the nitrous oxide flow rate is 7400sccm; the deposition time of the second silicon oxynitride layer 8 is 120s, the silane flow rate is 900sccm, the ammonia flow rate is 4000sccm, and the nitrous oxide flow rate is 8900sccm; the deposition time of the silicon oxide layer 6 is 100s, the silane flow rate is 900sccm, and the nitrous oxide flow rate is 11700sccm.

[0061] The experimental group includes a silicon substrate 1 and an aluminum oxide layer 2, a first silicon nitride layer 3 (thickness 12nm), a second silicon nitride layer 4 (thickness 22nm), a silicon oxynitride layer 5 (thickness 26nm) and a silicon oxide layer 6 (thickness 14nm) sequentially deposited on the silicon substrate 1, with a total film thickness of 74nm (the same as the control group) and a refractive index of 2.0. The specific preparation process is as follows:

[0062] An aluminum oxide layer 2 is first deposited on the front side of the silicon substrate 1; a first silicon nitride layer 3 is deposited on the aluminum oxide layer 2: a silane flow rate of 1700sccm, an ammonia flow rate of 10465sccm, a deposition time of 160s, and a silicon-nitrogen ratio of 16%; a second silicon nitride layer 4 is deposited on the first silicon nitride layer 3: a silane flow rate of 1150sccm, an ammonia flow rate of 10915sccm, a deposition time of 300s, and a silicon-nitrogen ratio of 11%; a silicon oxynitride layer 5 is deposited on the second silicon nitride layer 4: a silane flow rate of 1200sccm, an ammonia flow rate of 5200sccm, a nitrous oxide flow rate of 7400sccm, and a deposition time of 215s; a silicon oxide layer 6 is deposited on the silicon oxynitride layer 5: a silane flow rate of 900sccm, a nitrous oxide flow rate of 11700sccm, and a deposition time of 175s.

[0063] The other process steps of the experimental group and the control group are the same. The data of the TOPCon battery products prepared by the control group and the experimental group are shown in Table 1.

[0064] Table 1

[0065]

[0066]

[0067] It can be seen from Table 1 that compared with the control group, the short-circuit current Isc and conversion efficiency Eta of the improved process of the present application have been stably and significantly improved, indicating that the improved process has greatly improved the efficiency of TOPCon battery products.

[0068] In summary, a TOPCon battery front anti-reflection film structure and a preparation method thereof according to an embodiment of the present application have the following advantages: the present application changes the structure of the front anti-reflection film (from the conventional three-layer silicon nitride + two-layer silicon oxynitride + one layer of silicon oxide stacked structure to a two-layer silicon nitride + one layer of silicon oxynitride + one layer of silicon oxide stacked structure), and the total thickness of the structure remains unchanged, but the refractive index and thickness of the front silicon nitride layer are reduced (from the traditional 52nm to 34nm in the present application), and the refractive index of the total front structure is reduced from the original 2.08 to 2.0; because the TOPCON battery is an N-type substrate and there is no boron-oxygen compound with better anti-PID effect, this improvement will not have side effects on the battery cell, but enhances the absorption of front light, significantly improves the optical effect, and retains a good passivation effect, so that its short-circuit current gain is obvious, and the conversion efficiency is greatly improved.

[0069] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present application.

Claims

1. A TOPCon cell front anti-reflection film structure, comprising a silicon substrate (1) and an aluminum oxide layer (2) arranged on the silicon substrate (1), characterized in that: A first silicon nitride layer (3), a second silicon nitride layer (4), a silicon oxynitride layer (5) and a silicon oxide layer (6) are sequentially arranged on the aluminum oxide layer (2).

2. A TOPCon cell front anti-reflection film structure according to claim 1, characterized in that: The thickness of the first silicon nitride layer (3) is 10-14 nm, the thickness of the second silicon nitride layer (4) is 20-24 nm, the thickness of the silicon oxynitride layer (5) is 24-28 nm, and the thickness of the silicon oxide layer (6) is 12-16 nm.

3. A method for preparing the front anti-reflection film structure of a TOPCon cell as claimed in claim 1 or 2, characterized in that: The following steps are involved: S1, first depositing an aluminum oxide layer (2) on the front surface of a silicon substrate (1); S2, depositing a first silicon nitride layer (3) on the aluminum oxide layer (2), wherein the silicon-nitrogen ratio is 15%-17%; S3, depositing a second silicon nitride layer (4) on the first silicon nitride layer (3), wherein the silicon-nitrogen ratio is 10%-12%; S4, depositing a silicon nitride oxide layer (5) on the second silicon nitride layer (4); wherein the silicon-nitrogen ratio is 17%-19%; S5. Depositing a silicon oxide layer (6) on the silicon oxynitride layer (5), wherein the silicon-nitrogen ratio is 8%-10%.

4. The method for preparing a TOPCon cell front anti-reflection film structure according to claim 3, characterized in that: The deposition parameters of step S2 are: silane flow rate 1600-1800 sccm, ammonia flow rate 10000-11250 sccm, and deposition time 150-170 s.

5. The method for preparing a TOPCon cell front anti-reflection film structure according to claim 3, characterized in that: The deposition parameters of step S3 are as follows: silane flow rate 1000-1300 sccm, ammonia flow rate 10000-13000 sccm, and deposition time 280-320 s.

6. The method for preparing a TOPCon cell front anti-reflection film structure according to claim 3, characterized in that: The deposition parameters of the step S4 are: silane flow rate 1000-1200 sccm, ammonia flow rate 4900-5500 sccm, nitrous oxide flow rate 7000-7800 sccm, and deposition time 200-240 s.

7. The method for preparing a TOPCon cell front anti-reflection film structure according to claim 3, characterized in that: The deposition parameters of step S5 are: silane flow rate 800-1000 sccm, nitrous oxide flow rate 11200-12200 sccm, and deposition time 160-200 s.

Citation Information

Cited By

  • TOPCon battery preparation method for improving UVID and TOPCon battery

    CN121568469A

  • Improved UVID TOPCon cell fabrication method and TOPCon cell

    CN121568469B